ALAT PERAGA EDUKATIF DIGITAL SISWA DI MTS UNTUK VISUALISASI MATA PELAJARAN IPA - Tasya Gusti Amalia; Rohman Dijaya; Ade Eviyanti (Jurnal Informatika, 2023)
MTS darul huda is one of the tsanawia madrasah schools that are in jabon county. Like the madrasah tsanawia in general, the learning system at the madrasah tsanawia darul huda still USES the age-old method of using book study medium or images-picture 2d. This makes students saturated with learning especially like natural science subjects that require a realistic picture. According to current curriculum, referring to the 2013 revision of curriculum, the 2017 revision of the 2017 revision of the human body's anatomy materials are taught in eighth grade level, with the theme for human digestive materials that study the structure and function of human digestive systems. The expansion of the applications in augmented reality technology implementation methods in augmented reality as a augmented reality visual tool incorporating a multimedia development life cycle consisting of six stages: concept, design, material collection, manufacture, testing, The distribution of the marker or marker is a picture used to create 3d objects in a augmented reality system to generate a augmented reality app based on the overall result that the end result of the research, which is a digital educational display app for science at MTS darul huda and augmented reality reality can be run on the android device for Alt.